Analisis Pengaruh Harga Semen dan Tingkat Pendapatan Industri Batako Terhadap Permintaan Semen di Desa Pene Kecamatan Jerowaru: Analysis of the Influence of Cement Prices and Income Levels of the Brick Industry on Cement Demand in Pene Village, Jerowaru District - Kamaruddin (Pendidikan Al-Gafari, 2025)
In running its business, a company cannot avoid the existence of important problems in a company that disrupt the level of business health so that it will automatically disrupt the continuity of the business. The purpose of the researcher is to determine the effect of cement prices and income levels of the brick industry on cement demand in Selong Village. The type of research used in this study is a quantitative descriptive method. The sample in this study was taken using furvosive sampling, by determining Selong Village as a sub-population with the consideration that Selong Village has quite a lot of brick industry businesses, and the analysis tool used is multiple linear regression. The calculation results provide a regression equation for the brick industry: Y = 0.00466 + 0.00001587 X1 + 0 X2 + e Thus, if there is an increase in the price of cement, it will cause a decrease in demand for cement by -1 sack / month, assuming that other variables are constant or ceteris paribus while the income level variable increases by Rp. 1,000 then there is no increase in demand by 0 sacks / month. The results of the study also obtained a description that the average net income level of brick entrepreneurs is Rp. 14,042,883 per month. The results of this study suggest that efforts should be made to suppress sales in full capacity, meaning that sellers should not work half a day but rather try to sell out the bricks they print. In addition, development is also needed so that it can be an example for other small entrepreneurs.